A comparative analysis of vehicle-related greenhouse gas emissions between organic and conventional dairy production. Issue 3 (23rd August 2017) - Aggestam, Vivianne; Buick, Jon
Abstract : Agricultural industrialisation and globalisation have steadily increased the transportation of food across the world. In efforts to promote sustainability and self-sufficiency, organic milk producers in Sweden are required to produce a higher level of cattle feed on-farm in the hope that increased self-sufficiency will reduce reliance on external inputs and reduce transport-related greenhouse gas emissions. Using data collected from 20 conventional and 20 organic milk producers in Sweden this paper aims to assess the global warming impact of farmyard vehicles and the transportation of feed produced 'off-farm' in order to compare the impact of vehicle-related emissions from the different production methods. The findings show organic and conventional production methods have different vehicle-related emission outputs that vary according to a reliance on either road transportation or increased farmyard machinery use. Mechanical weeding is more fuel demanding than conventional agrichemical sprayers. However, artificial fertilising is one of the highest farmyard vehicle-related emitters. The general findings show organic milk production emits higher levels of farm vehicle-related emissions that fail to be offset by reduced emissions occurring from international transport emissions. This paper does not propose to cover a comprehensive supply chain carbon footprint for milk production or attempt to determine which method of production has the largest climatic impact. However, it does demonstrate that Sweden's legal requirements for organic producers to produce more feed on-farm to reduce transport emissions have brought emissions back within Sweden's greenhouse gas inventory and raises questions around the effectiveness of policies to reduce vehicle-related emissions. Further research is needed into the effectiveness of climate change mitigation on food production policies, in particular looking at various trade-offs that affects the entire food supply chain.